Are firewood preference behaviors influenced by restrictions in access to vegetation, and can they vary over time? - Tavares Mendes, Carlos Henrique; Alves Ramos, Marcelo; Silva, Taline Cristina (Ethnobiology and Conservation, 2024)
Studies aim to understand the behavior of human populations when selecting certain groups of plants over others. Some plants are chosen for favorable characteristics that justify specific uses. Thus, individuals may exhibit specialized behavior patterns, selecting plants for fuel based on specific biological traits like ignition potential and durability, or generalized behavior patterns, depending on species availability or utilitarian redundancy. However, little is known about how the preference for these resources may be shaped by contexts that prohibit resource use. Prohibiting resource use can compel human groups to devise new selection strategies, leading to significant changes in socioecological system dynamics. Hence, this study aims to investigate how preference for plants used as firewood varies in areas with restricted and unrestricted resource use. We conducted semi-structured interviews in two communities. Participants with restricted natural resource access in the past showed a tendency towards specialized behavior (p<0.000849). However, due to imposed restrictions, the community had to develop new usage strategies, resulting in a tendency towards generalized behavior (p>0.6489). Preference in unrestricted use areas varied over years, with generalists in the past (p>0.4675) and specialists presently (p<0.2074). Based on these behaviors, we infer that these human groups possess adaptive plasticity to mitigate the drastic effects of long-term wood resource extraction.